Trajetória histórica da criação dos cursos técnicos de enfermagem da Universidade Federal do Piauí - Marinelli, Natalia Pereira (2020)
The interest in the study of historical facts is old. Studying the historical trajectory is especially important because it allows us to know the past, the different relationships among social groups, as well as to understand the way of transformation of the human being in its most diverse contexts. The Federal University of Piauí has three linked Technical Colleges: Technical College of Teresina, Technical College of Floriano and Technical College of Bom Jesus. There are not enough registers, scientific studies and researches that approach the historical trajectory of the creation of the nursing technical courses of the Federal University of Piauí, portraying the difficulties, conquests and facts that impelled or delayed this process. The general objective of the study is to analyze the historical trajectory of the creation of the nursing technical course in the three schools of University Federal of Piauí. It is a sócio-historical research of qualitative character, using the analysis of documents and field research through the technique of interviews, with those involved in the process of creating the technical courses of UFPI, based on the resources offered by the Thematic Oral History for its implementation. The first coordinators of the technical nursing courses, members of the commissions designated for the creation of the courses and for the elaboration of the Project for its creation, the first teachers, the directors of the schools of the occasion and some teachers of the courses of the time of creation were part of the study, totaling 11 collaborators. The product of the analysis resulted in four categories: The prelude of the technical nursing courses at UFPI; physical structure and working conditions; relationship with the community, rectory and other courses; and student-teacher relationship. Regarding the factors that drove the creation and origin of the course, it was discovered that, besides the local demand, there are the political interests of the institution itself and the request by the community. The first UFPI Technical Nursing Course was designed to be installed in Floriano. The physical and material resources for the beginning of the classes were satisfactory for the time and the relationship between teachers and students occurred in an affectionate way, with respect, confidence and complicity. The results of this research brought relevant information to the knowledge of the origin of the technical courses of nursing of the referred University. In this way, recognizing the importance of the historical rescue for the consolidation of the course and the profession, it is that corroborates the value of this study for the preservation of the memory of nursing professionals, becoming also an important component of the history of students and teachers of this course.